2021
DOI: 10.3390/v13061120
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Antivirals Using Phage Display

Abstract: The latest coronavirus disease outbreak, COVID-19, has brought attention to viral infections which have posed serious health threats to humankind throughout history. The rapid global spread of COVID-19 is attributed to the increased human mobility of today’s world, yet the threat of viral infections to global public health is expected to increase continuously in part due to increasing human–animal interface. Development of antiviral agents is crucial to combat both existing and novel viral infections. Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 218 publications
(241 reference statements)
1
8
0
Order By: Relevance
“…Frontiers in Microbiology 06 frontiersin.org pathogen invasions in this lab (Zhao et al, 2012) or others (Hall et al, 2009;Wei et al, 2020). This study and several other efforts (Anand et al, 2021;Sokullu et al, 2021;Ballmann et al, 2022;Labriola et al, 2022;Petrenko et al, 2022;Sevenich et al, 2022;Yang et al, 2022) demonstrated that PhD was a plausible method for generating possible therapeutics to treat COVID-19 as well. For example, Petrenko used phage-displayed spike S1 protein mimotopes to search for "all" cellular receptors, including authentic and alternative ones.…”
Section: Synthetic C2 and C6 Peptides Blocked The Binding Of Spike-tr...supporting
confidence: 60%
“…Frontiers in Microbiology 06 frontiersin.org pathogen invasions in this lab (Zhao et al, 2012) or others (Hall et al, 2009;Wei et al, 2020). This study and several other efforts (Anand et al, 2021;Sokullu et al, 2021;Ballmann et al, 2022;Labriola et al, 2022;Petrenko et al, 2022;Sevenich et al, 2022;Yang et al, 2022) demonstrated that PhD was a plausible method for generating possible therapeutics to treat COVID-19 as well. For example, Petrenko used phage-displayed spike S1 protein mimotopes to search for "all" cellular receptors, including authentic and alternative ones.…”
Section: Synthetic C2 and C6 Peptides Blocked The Binding Of Spike-tr...supporting
confidence: 60%
“…Phage display is a feasible method for selection of a particular domain of an antigen. 41,42 Through the construction of a large-capacity natural nanobody-gene library, a variety of nanobodies can be prepared without…”
Section: Discussionmentioning
confidence: 99%
“…The resulting immune library does not need to be as large as naïve libraries, since the immunized pool of lymphocytes would contain multiple proliferated B-cell clones targeting the antigen. Some naïve antibody libraries represent 10 11 individual clones or more [ 18 , 21 , 22 ], reaching practical limit of the phage antibody library size preset around 10 12 value, due to the technical limitation of bacterial transformation, culturing, and storage [ 62 ]. While theoretical diversity of the naïve combinatorial libraries is much higher than their achievable size, there is significantly less variety of the naturally paired VH-VLs in the mammalian immune system.…”
Section: M13 Phage Antibody Librariesmentioning
confidence: 99%
“…Since Smith and Winter published their pivotal studies in 1980s-1990s [ 9 - 14 ], the scope and capabilities of phage display have been enormously expanded [ 15 - 20 ]. Construction of large numbers of phage display peptide and antibody libraries containing 10 11-12 unique members have been achieved [ 18 , 21 , 22 ] and are commercially available (New England BioLabs, MoBiTec GmbH, and Creative Biolabs, Shirley, NY, USA)…”
Section: Introductionmentioning
confidence: 99%